NGHIÊN CỨU ĐỀ XUẤT MÔ HÌNH XỬ LÝ KIM LOẠI NẶNG (Pb, Cd) TRONG BÙN THẢI KÊNH RẠCH BẰNG THỰC VẬT - Vũ, Mạnh; Trần, Văn Trưởng; Nguyễn, Bảo Ngọc (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY TO PROPOSE THE TREATMENT MODEL FOR HEAVY METALS (Pb, Cd) IN CANAL SLUDGE BY USING PLANTS In the article a treatment model of heavy metal (Pb, Cd) in sludge of B Canal and Tân Hóa - Lò Gốm Canal of Ho Chi Minh City by using plants is proposed. It is found that Vetiveria zizanoides, Strelitzia reginae, Heliconia psittacorum can live and absorb Pb, Cd in sludge of the canals. Heliconia psittacorum and Vetiveria zizanoides absorb the metals mainly by their roots, while Strelitzia reginae uses their roofs and trunks. The planting trial shows that both Heliconia psittacorum and Vetiveria zizanoides live well in sludge of the canals. Vetiveria zizanoides absorbs Pb and Cd better than Heliconia psittacorum and can be used in model for treating Pb, Cd contaminated sludge.